Analisis Perbandingan Rasio Solvabilitas Pada PT. Fortune Indonesia, Tbk Dengan PT. Surya Citra Media, Tbk - Abdul Haris; Nurhayati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the differences in Debt to Asset Ratio, Debt to Equity Ratio between PT. Fortune Indonesia Tbk and PT. Surya Citra Media, Tbk. The population in this study was 19 years old, while the sample used was 10 years old. The statistical tool used is SPSS V 26 with the Independent Sample Test. The results of this research show that there is no significant difference in Debt to Asset Ratio between PT. Fortune Indonesia Tbk and PT. Surya Citra Media, Tbk and There is a significant difference in Debt to Equity Ratio between PT. Fortune Indonesia Tbk and PT. Surya Citra Media, Tbk.